The digger wasps of the genus Prionyx Vander Linden (Hymenoptera: Sphecidae) of Russia and Central Asia, with a key to species, new synonymies, and lectotype designations - Danilov, Yuriy N. (Zootaxa, 2012)
Seventeen species of Prionyx Vander Linden, 1827 are recorded from Russia and Central Asia. The new synonymies proposed are Sphex haberhaueri Radoszkowski 1871 =Enodia vittata Kohl 1884, syn. nov.; Sphex niveatus Dufour 1854 =Podium maracandicum Radoszkowski 1877, syn. nov., =Sphex afghaniensis de Beaumont 1970, syn. nov.; Sphex viduatus Christ 1791 =Sphex leuconotus F. Morawitz 1890, syn. nov.; Enodia argentata Mocsáry 1883 =Sphex gobiensis Tsuneki 1971, syn. nov. The lectotypes are designated for ten species: Podium maracandicum Radoszkowski 1877, Sphex sirdariensis Radoszkowski 1877, Sphex stschurowskii Radoszkowski 1877, Sphex persicus Mocsáry 1883, Sphex hispidus F. Morawitz 1890, Sphex leuconotus F. Morawitz 1890, Sphex melanotus F. Morawitz 1890, Sphex tenuicornis F. Morawitz 1890, Sphex suavis F. Morawitz 1893, and Sphex zarudnyi Gussakovskij 1933. A key to the species is given.